2018
DOI: 10.1007/s10815-018-1376-1
|View full text |Cite
|
Sign up to set email alerts
|

Infertility patients with chromosome inversions are not susceptible to an inter-chromosomal effect

Abstract: Purpose The aim of this study was to evaluate the incidence of an inter-chromosomal effect (ICE) in blastocyst-stage embryos from carriers of balanced chromosome inversions. Methods Infertility patients (n = 52) with balanced inversions (n = 66 cycles), and maternal age-matched controls that concurrently cycled (n = 66), consented to an IVF cycle with preimplantation genetic testing for aneuploidy (PGT-A). Blastocyst-stage embryos underwent trophectoderm biopsy for PGT-A with only euploid blastocysts transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Our observations showed that there were no statistically significantly differences in de novo aneuploid rates between pericentric and paracentric inversion carriers. As is well-known, the production of de novo aneuploids is closely related to maternal advanced age, and the interchromosomal effect is inconspicuous just as many studies indicated [7,21]. Therefore, paracentric inversion cannot be considered less pernicious than pericentric inversion in genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations showed that there were no statistically significantly differences in de novo aneuploid rates between pericentric and paracentric inversion carriers. As is well-known, the production of de novo aneuploids is closely related to maternal advanced age, and the interchromosomal effect is inconspicuous just as many studies indicated [7,21]. Therefore, paracentric inversion cannot be considered less pernicious than pericentric inversion in genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Inversion carriers with small distal segments of the inverted chromosome are more likely to give birth to chromosomally unbalanced or phenotypically abnormal offspring. Accordingly, inversion heterozygotes in which one or both distal segments are large have a risk for producing gametes and recombinants with considerable genetic imbalance, leading to implantation failure or pregnancy loss [7]. Besides, there are other factors such as the location of breakpoints that are likely to affect the chance of inversion loop formation as well [6].…”
Section: Introductionmentioning
confidence: 99%
“…Inversion carriers with small distal segments of the inverted chromosome are more likely to give birth to chromosomally unbalanced or phenotypically abnormal offspring. Accordingly, inversion heterozygotes in which one or both distal segments are large have a risk for producing gametes and recombinants with considerable genetic imbalance, leading to implantation failure or pregnancy loss [6].…”
Section: Introductionmentioning
confidence: 99%
“…The chromosomes of embryos fertilized by abnormal gametes can result in a partial monosomy or a trisomy represented as congenital defects [7]. The frequency of recombination within the gametes is related to parameters such as the involved chromosome, the location of breakages, the size of the inverted segment and its proportion in relation to the size of the whole chromosome [8].…”
Section: Introductionmentioning
confidence: 99%